Intracellular sorting and transcytosis of the rat transferrin receptor antibody OX26 across the blood–brain barrier in vitro is dependent on its binding affinity. Issue 6 (16th August 2018) - Haqqani, Arsalan S.; Thom, George; Burrell, Matthew; Delaney, Christie E.; Brunette, Eric; Baumann, Ewa; Sodja, Caroline; Jezierski, Anna; Webster, Carl; Stanimirovic, Danica B.
Abstract: The blood–brain barrier (BBB) is a formidable obstacle to the delivery of therapeutics to the brain. Antibodies that bind transferrin receptor (TfR), which is enriched in brain endothelial cells, have been shown to cross the BBB and are being developed as fusion proteins to deliver therapeutic cargos to brain targets. Various antibodies have been developed for this purpose and their in vivo evaluation demonstrated that either low affinity or monovalent receptor binding re‐directs their transcellular trafficking away from lysosomal degradation and toward improved exocytosis on the abluminal side of the BBB. However, these studies have been performed with antibodies that recognize different TfR epitopes and have different binding characteristics, preventing inter‐study comparisons. In this study, the efficiency of transcytosis in vitro and intracellular trafficking in endosomal compartments were evaluated in an in vitro BBB model for affinity variants ( K d from 5 to174 nM) of the rat TfR‐binding antibody, OX26. Distribution in subcellular fractions of the rat brain endothelial cells was determined using both targeted quantitative proteomics‐selected reaction monitoring and fluorescent imaging with markers of early‐ and late endosomes. The OX26 variants with affinities of 76 and 108 nM showed improved trancytosis (Papp values) across the in vitro BBB model compared with a 5 nM OX26. Although ~40% of the 5 nM OX26 and ~35% of TfR co‐localized with late‐endosome/lysosome compartment, 76 and 108 nM affinity variants showed lower amounts in lysosomes and a predominant co‐localization with early endosome markers. The study links bivalent TfR antibody affinity to mechanisms of sorting and trafficking away from late endosomes and lysosomes, resulting in improvement in their transcytosis efficiency. Open Science Badges: This article has received a badge for *Open Materials* because it provided all relevant information to reproduce the study in the manuscript. The complete Open Science Disclosure form for this article can be found at the end of the article. More information about the Open Practices badges can be found athttps://cos.io/our-services/open-science-badges/ . Cover Image for this issue: doi:10.1111/jnc.14193 . Abstract : Antibodies that bind transferrin receptor (TfR) can cross the tightly sealed blood–brain barrier (BBB) and deliver therapeutic payloads into the brain. This study shows that lowering the affinity of the TfR antibody OX26 re‐directs its intracellular traffic in brain endothelial cells (BEC) from degradative lysosomal pathway toward early and recycling endosomes. This results in facilitated transport of lower affinity OX2676, compared to high‐affinity OX265, across the BBB model in vitro . Bioengineering TfR antibodies to optimize their affinity can improve their ability to deliver therapeutics across the BBB. Cover Image for this issue: doi:10.1111/jnc.14193 . Open Science: This manuscript was awarded with the Open Materials Badge For more information see:https://cos.io/our-services/open-science-badges/